Invasive Plant Biomass as a Source of Lipids for Bioeconomy - Borska Eva; Kviesis Jorens; Ansone-Bertina Linda; Klavins Maris (Environmental and Climate Technologies)
Invasive plants can be considered as a significant environmental problem: a direct threat to biodiversity but also affecting the productivity of agriculture forestry as well as human and animal health. Considering the threats by invasive plants European as well as other countries put efforts into invasive plant spreading control and eradication of existing populations. Invasive plant biomass at the same time can be a valuable resource for bioeconomy. The study aims to evaluate the possibilities of using invasive plant biomass as a source of biologically and pharmacologically active substances – lipids and fatty acids. Invasive plants common in North Europe have been studied: lupine, Canadian goldenrod and Japanese, Bohemian and Sakhalin knotweeds. For extraction traditionally used solvents were compared with green (low toxicity, biogenic origin) solvents and the good performance of the environmentally friendly solvents has been demonstrated. Bohemian knotweed exhibits higher proportions of certain fatty acids such as linoleic acid and eicosanic acid in comparison to other species. Japanese knotweed, on the other hand, generally displays intermediate levels for most fatty acids but stands out with distinct peaks in components such as linolenic acid. In contrast, Sakhalin knotweed dominates in several fatty acids including palmitic acid which highlights its unique biochemical profile. Thus, invasive plants can serve as valuable resources of biologically active compounds for differing applications and their biomass biorefinery can serve as a resource thus supporting invasive plant eradication efforts.